(3TQM bUjOI HQOI GdeOjM ddHhUjQis - (3Ydj Hf CMeO GdHNGQjs; (3eMeO Hf SYjO Hf MeGO GdUfgGLj GdHhUjQj, (B696 (3g`,J (B696 (3g` s ((3Ydi Hf eMeO GdHNGQi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd eMHI fHjI hSjdI efLGI hHYO aEf GdhSGFd Edi GdMVQI GdCMOjI hGdPQGFY LeYI dGJVHW CYOGOgG s
(3BNQgG (B:s
(3CeG GdhLg aj GdChd adGf GdUHG eNUhU HGdfHi Udi Gddg Ydjg hSde CeG GdhLg aj GdKGfi adjhWfgG aj GdfaS Je s
(3Vef eLehY s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B11s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3eJaQbGJs